Association Between Duration of Human Immunodeficiency Virus (HIV)–1 Viral Suppression Prior to Renal Transplantation and Acute Cellular Rejection. Issue 2 (19th September 2016) - Husson, J.; Stafford, K.; Bromberg, J.; Haririan, A.; Sparkes, T.; Davis, C.; Redfield, R.; Amoroso, A.
Abstract : Renal transplant has become an important option for human immunodeficiency virus (HIV)–infected patients with end‐stage renal disease; however, these patients experience a high rate of acute cellular rejection (ACR). Guidelines do not currently exist for the optimal duration of viral suppression prior to transplantation. In a retrospective cohort analysis of 47 HIV‐infected renal transplant recipients, we compared the rate of ACR between patients based on the length of time of viral suppression prior to transplantation. Of the patients who achieved viral suppression for >6 months but less than 2 years prior to transplantation (n = 15), 60% experienced ACR compared to 41% of patients suppressed at least 2 years or more (n = 32) prior to transplant (p = 0.21). Patients suppressed <2 years experienced ACR at 2.48 times the rate of those suppressed 2 years or longer. Induction immunosuppression, HLA mismatch and panel‐reactive antibodies (PRAs) did not significantly differ between the two groups. Abstract : A longer duration of HIV viral suppression before renal transplantation may lead to lower rates of acute cellular rejection posttransplantation.